ONLINE PARENT-CHILD INTERNET ADDICTION TEST SCREENING & SCORING USING GOOGLE FORM & GOOGLE SHEET - Tissa Maharani (Asosiasi Dosen Muda Indonesia, 2024)
The use of gadgets, which has increased significantly due to technological developments and the post-Covid-19 pandemic, has negative effects that can lead to addiction, both in adults and children. Gadget addiction is characterized by a person's inability to separate from their gadget. Before being declared to have gadget addiction, a test must first be carried out by a psychologist. This test is called PCIAT (Parent-Child Internet Addiction Test), which is based on PIMU (Problematic Interactive Media Use) criteria, and developed based on the Internet Addiction Test that has been widely used in clinical assessment. Currently, the PCIAT is web-based but still in English, while the one that has been translated into Indonesian is still conducted by psychologists manually using paper, which becomes inefficient and ineffective when faced with a large number of people taking the test. This research aims to make PCIAT screening and scoring online using Google Form and Google Sheet, so that it can be easily used by professionals and the public massively at one time, quickly, and reduce the use of paper. The result of this research, the availability of online PCIAT created using Google Form and Google Sheet, which is easy to use massively and faster in obtaining and processing screening data, so that it is faster to provide the analysis needed by psychologists.